Digital Business Development Strategy in Modern Global Market - Sri Asmirani (STIE Amkop Makassar, 2024)
In the era of rapid technological advancements and globalization, businesses face unprecedented challenges and opportunities. Digital business development has become a cornerstone for achieving competitiveness and sustainability in the modern global market. This paper explores strategies for digital business growth, focusing on leveraging emerging technologies, enhancing customer experiences, and optimizing operational efficiency. Key components include digital transformation, data-driven decision-making, omnichannel marketing, and the integration of artificial intelligence and automation. Case studies from successful global businesses illustrate the impact of these strategies on market expansion, customer retention, and revenue growth. The findings underscore the necessity of agility, innovation, and strategic collaboration in navigating the complexities of the digital economy.